2021
DOI: 10.2147/prbm.s324233
|View full text |Cite
|
Sign up to set email alerts
|

Fear, Anxiety, Stress, and Depression of Novel Coronavirus (COVID-19) Pandemic Among Patients and Their Healthcare Workers – A Descriptive Study

Abstract: Purpose Disease pandemics are known to cause psychological distress. The ensuing mental health issues are not only restricted to the patients and their relatives/friends but affect the healthcare workers (HCWs) as well. Our study aims to assess these psychological trends during the COVID-19 pandemic between the two most affected population groups, that is, patients and frontline healthcare workers. Patients and Methods A survey questionnaire, including scales to assess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Health care workers’ mental health problems increased because of irregular working hours, higher levels of exposure to illness, fear of infection and lack of adequate PPE, amongst others (World Health Organization, 2021 ; Yang et al, 2021 ). Anxiety and depression were mental health problems frequently experienced, with insomnia, sleeping disorders and burnout as risk factors (Chen et al, 2021 ; World Health Organization, 2021 ), and these are often reported by workers who work with COVID-19 patients (Parchani et al, 2021 ; Vagni, Maiorano, Giostra, & Pajardi, 2020 ; Van Roekel et al, 2021 ). During this pandemic, traumatic stress in health care workers was also related to moral injury, because they were often facing difficult conditions in making decisions (Litam & Balkin, 2021 ), especially those with clinical responsibility (Parthasarathy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Health care workers’ mental health problems increased because of irregular working hours, higher levels of exposure to illness, fear of infection and lack of adequate PPE, amongst others (World Health Organization, 2021 ; Yang et al, 2021 ). Anxiety and depression were mental health problems frequently experienced, with insomnia, sleeping disorders and burnout as risk factors (Chen et al, 2021 ; World Health Organization, 2021 ), and these are often reported by workers who work with COVID-19 patients (Parchani et al, 2021 ; Vagni, Maiorano, Giostra, & Pajardi, 2020 ; Van Roekel et al, 2021 ). During this pandemic, traumatic stress in health care workers was also related to moral injury, because they were often facing difficult conditions in making decisions (Litam & Balkin, 2021 ), especially those with clinical responsibility (Parthasarathy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The early months of pandemic had the higher reported prevalence of stress with a significant proportion of individuals reporting being upset due to things happening unexpectedly, inability to overcome difficulties in daily life, and anger at things being outside their control. Among suspected patients, those with history of travel to areas with ongoing community transmission were found to display greater stress [15]. Patients who are kept in isolation and quarantine experience significant levels stress as well [2].…”
Section: Stress Among Patient Populationmentioning
confidence: 98%
“…Socio-demographic variables play a key role in determining the level of anxiety in healthcare workers with higher prevalence among those above the age 40, females, unmarried individuals and presence of offspring [38]. Anxiety in this group manifests as palpitations, tremors, dryness of Mental Impact of COVID-19 -Fear, Stress, Anxiety, Depression and Sequels DOI: http://dx.doi.org/10.5772/intechopen.102754 mouth, feeling scared without any reason and tendency to panic [15]. These symptoms are more prevalent in workers who were assigned duties in COVID designated areas and those who encountered SARS-CoV2 suspected or confirmed patients without adequate protection [5].…”
Section: Anxiety Among Hcw Populationmentioning
confidence: 99%
“…Information about COVID-19 has been shown to induce threat, stress, depression, and anxiety (e.g., Parchani et al, 2021; Salari, et al, 2020), which can subsequently trigger a defensive reaction in an effort to reduce negative emotional states and regain a feeling of control (Kellstedt, et al, 2008; White & Dillon, 2000). Believing that you respond according to medical recommendations more than other people serves this purpose very well.…”
Section: Comparing With Others In a Moment Of Crisis: Better-than-ave...mentioning
confidence: 99%